Active films based on starch and wheat gluten (Triticum Vulgare) for shelf-life extension of carrots (2022)
The use of biodegradable biopolymers with the incorporation of active ingredients has been considered as an alternative to extend the useful life of food. Therefore, the objective of this research was to develop active films based on starch and wheat gluten, containing cinnamon and turmeric essential oils by using the solvent casting method. Different film formulations were made from wheat starch, gluten, glycerol, and essential oils of cinnamon and turmeric. The films were characterized according to their morphology, optical, thermal, antioxidant, and barrier properties. Subsequently, the active properties on baby carrots regarding weight loss, appearance, and fungal growth were evaluated. The results indicated that the starch-based films showed a slight decrease in moisture content with the addition of essential oils (up to 13.29%), but at the same time showed a significant reduction in water solubility (up to 28.4%). Gluten-based films did not present significant differences in these parameters, although the solubility in water tended to increase (up to 13.15%) with the addition of essential oils. In general, the films presented good thermal stability and antioxidant capacity, and in the carrot coating test, a decrease in weight loss of up to 44.44% and 43.33% was observed for the coatings based on starch and gluten with the addition of turmeric essential oil, respectively. Finally, films developed with cinnamon and turmeric essential oils are potential candidates for the design of biodegradable active packaging.